Comparative study between two industry-standard flood modelling software packages - Pricynthia Biusti (2022)
Flooding is amongst the most common natural disasters on the world. 1D modelling tools for hydraulic design make simplifying assumptions that may result in overly cautious, insufficient, or incorrect findings and conclusions. In the other hand, tools for 2D hydraulic modelling are widely accessible and continue to develop as technology develops. The Joint Defra (Department for Environmental, Food, and Rural Affairs) Environment Agency of the United Kingdom (UK) created a series of benchmark tests for 2D modelling as a result. The dataset for the test has been used in this project to compare the performances of HEC-RAS and RiverFlow2D. Total of three tests conducted in this project using HEC-RAS while the result for RiverFlow2D is obtained from previous researchers. Diffusion Wave Equation (DWE) and Shallow Water Equation (SWE) have been used in HEC-RAS to run the test. Based on the three tests, both software showed well performances in running the test include when using complicated terrain profile as the Data Elevation Model (DEM). However, when comparing the result obtained from both software, RiverFlow2D performed well than HEC-RAS. The succession of HEC-RAS and RiverFlow2D to run the test showed that both software can do the prediction and simulation of flooding.